Kewenangan dan Tanggung Jawab Notaris Dalam Pembuatan Akta Pernyataan Keputusan Rapat Yayasan Yang Tidak Memenuhi Kuorum - Melvina Aldhia Assyauqi; Ramlani Lina Sinaulan; Putra Hutomo (JOURNAL of LEGAL RESEARCH, 2022)
Notaries have jurisdiction under Article 15 of the UUJN and responsibility under Article 16 of the UUJN. A Notary's responsibilities extend beyond his own, as he is a public authority authorized to make a genuine deed. Because the Notary's negligence will have legal ramifications for the deed he made. Notaries must also follow all applicable laws and regulations while preparing the Deed of Statement of Foundation Meeting Resolutions. This study used the library research approach, which involves looking through library materials or secondary data. This project will discover, explain, and categorize library materials that provide information pertinent to the concerns presented. According to the research, a Notary's principal authority is to make a genuine document, which might be an official deed (relaas) or a party deed (partij). The UUJN controls a Notary's particular authority, which is to provide legal advice in connection with the making of a deed. The Foundation Law must be followed while drafting the Deed of Statement of Foundation Meeting Decisions based on the Trustees meeting decision. Deed of Statement of the Foundation Meeting Resolutions whose minutes do not reach the quorum are subject to sanctions such as cancellation of the deed.